CEMETERY TOURISM IN LOURES: THE VALUE OF THE TRANSFIGURATION OF A CEMETERY - Assunção, Ana Paula (2019)
The western necropolis has been structured around a texture of signs and symbols that evoke the memory of the past, on the one hand, and, on the other hand, bring to the present ancient rituals of the search for eternity that have been reproduced since the 18th century. Taking into consideration constant memories, proto-memory, and the philosophy of memory, the fact is that the evocation of what is absent has led to different discourses such as its transfiguration into cultural and tourism assets on a global scale. Since the end of 1990s, the various uses of a cemetery have been emphasized and resulted in differentiated concepts and perspectives regarding tours at the site. As such, it is now common to consider there is a wide set of attitudes vis a vis death and its records. One of the reasons and motivations for this research is also the growth and diversification of the tourist offer. This article compiles the existing scientific information on tourism, specifically cemetery tourism, analyses the above-mentioned approaches; and uses as case study the Loures Municipal Cemetery, in order to draw reliable conclusions and contribute to scientific research in this specific field. One of the main finding aspects of the observation is the hypothesis regarding the possibility of developing cemetery tourism in non-Romantic cemeteries, as it is the case with the Loures Cemetery.